ENHACEMENT OF SWIMMING KINEMATICS AND PERFORMANCE THROUGH PROPRIOCEPTION - POP, Nicolae Horațiu; ILISEI , Irina (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2022)
Proprioception is closely linked to control of movement, and it has been shown that athletic performance is based on good proprioceptive abilities. The purpose of this study was to examine whether the weighting of the fist joints (in the form of weighted fabric wrist cuffs) has an impact on the swimming technique and thus on performance in freestyle swimming. A number of 16 male subjects with a medium age of 20.74 years took part in our study and were distributed into 2 separate groups: experimental group and control group. Calculations were made using descriptive statistics and the data for the participating subjects proved to be statistically relevant. Using stimulating elements for proprioception can render positive effects on the swimming technique in freestyle swimming and thus on athletes’ performance.